Possibilities for Using E-Modules in Vocational High Schools to Facilitate Critical Thinking Skills - Eka Fitriana; Djono Djono; Sri Sumaryati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Critical thinking as part of the competency tools for 21st-century positions has a strategy at the Vocational high school in preparing graduates who are competent, ready to work, and have communication and collaboration skills. However, learning media use still needs to be optimal for teachers to support classroom learning to increase students' understanding and facilitate critical thinking skills in the learning process. Therefore, it is necessary to improve the learning system because these problems must provide students with a better learning experience. The research aims to determine students' perceptions regarding opportunities for developing e-modules based on problem-based learning to facilitate critical thinking skills in accounting learning material. Method: Descriptive qualitative, using research instruments like interviews and questionnaires. The research participants were 45 students specializing in accounting. The research results showed that students are very familiar with using digital media, and most students said that learning with digital learning media gave an interesting learning impression. Results: are great opportunities for developing e-modules that students can use for independent learning flexibly. Novelty: E-modules integrated with problem-based learning models aim to empower students' critical thinking skills, especially in accounting material.